(untitled) (Journal of Economic Research & Business Administration, 2016)
The article considers the issues of currency-financial integration, which is necessary and appropriate step in development and strengthening EAEU under the world economic crisis. It is necessary to set unified rules of currency regulation and payment-account operations, coordinated monetary and tax policy. The opportunity to enact common currency in order to decrease expenses of of trade operations and for economic stabilization EAEU countries, which will lead to decrease costs and mutual investments risks, stabilization of inflation and interest rate, when the borrowing cost will also decrease, which very important for small economies of EAEU. It should be noted that the integration processes in the EAEC develop in quite difficult conditions when global problems are aggravated in politics and economics, and politics increasingly affect the economy. In this situation, win only a powerful integration module.